«Amnesia in Fancy Dress»: il pageant in Between The Acts di Virginia Woolf e in Wigs on the Green di Nancy Mitford (ACME, 2021)
This essay aims at analysing the role of the pageant within two novels of the interwar period: Virginia Woolf’s Between the Acts (1941) and Nancy Mitford’s Wigs on the Green (1935). Pageants have played a fundamental role in interwar England as symbols of both the English tradition and Englishness, also becoming the focus of 1930s English literature. In Between the Acts, Miss La Trobe’s historical pageant performed «in the heart of the [English] country», on the lawn of Pointz Hall, shows the inescapable chaos of the modern human condition and the sense of loneliness and isolation of English society on the brink of WWII. Mitford, instead, uses the pageant to unmask the insubstantial ideology of interwar English fascism, dismissed by her as «empty rhetoric», and represented, in Wigs on the Green, by the figure of Eugenia Malmains, «England’s largest heiress» – the fictional version of Nancy’s fascist sister, Unity Valkyrie – and an ardent supporter of Captain Jack and the Union Jackshirts movement, the fictitious equivalent of Sir Oswald Mosley’s British Union of Fascists. After a brief introduction on the function of the pageant in 1930s English literature, I move to its contextualisation in the aforementioned novels, focusing in particular on its meaning within the historical, cultural and social milieu.